Inevitable Scars; A Study on Traumatic Verbal, Emotional and Physical Abuse Distressing Females - Syeda Farah Batool; Shamoon Noushad; Maria Altaf; Sadaf Ahmed (International Journal on Women Empowerment, 2016)
Women, a name that embraces love respect and honor but unfortunately in the setup of our society it is not applicable as Islam is deliberately pulverized and entwined by socio cultural norms and personal beliefs. The aim of this study was to identify the common psycho-social perspectives among victims exposed such insults in relation with psychosocial correlates. A general survey based study was conducted and females with the age range of 18 to 50 years were interviewed on a predesigned questionnaire with analysis of variables like stress, type of abuse, age of victimization and painful memories. The results were calculated using SPSS VERSION 20. 50% of total respondents has reported Emotional abuse, 24% has reported sexual assault while 25% of them has reported domestic violence. There might be several reasons behind this ill practice in society from socio cultural barrier to mal practice of religious domains. These variables of abuse are not only the mere threats to psychological wellbeing of victims but also have an indirect effect on their prime roles in society as a suppressed entity. Studies have revealed that the causes of exploitation physical or mental from men to women are generally Obedience from the women, Outrage of frustration, Inferiority complex, Psychological disorder, Un-controllable sex desire & Superiority syndrome.